MANAJEMEN DAN KEPEMIMPINAN DALAM ISLAM - Zilazaini; Nurul Ardila; Riana Anjani; Silitonga, Serli Pitriyani; Safitri, Rima Eka (Department of Islamic Education Management, 2022)
Leaders and leadership are a unit that is difficult to separate, because there is no leader without leadership, while a leader will be meaningless without a leader. To carry out leadership properly and correctly and to create prosperity, a leader must have basic principles that must be possessed as a basis for thinking and acting. Islamic leadership is a balance between leadership with worldly and ukhrowi concepts, achieving essential goals more than just temporary organizational goals, demands a high commitment to Islamic principles and places the task of leadership not only as a humanitarian task that is accountable only to members, but also before Allah SWT.